C. P. E. Bach: Sonatas with Varied Reprises, Wq 50 - Zafeiropoulos, Anastasios (Mechelen Evil Penguin Classic, 2024)
Tom Beghin, clavichord2 CDsEvil Penguin Classic2024 EPRC 0066Recorded April 2–4, 2024, at Motormusic (Mechelen, Belgium)Sound recording: Steven Maes, with George Georgiev and Lowie PeetersArtistic supervision: Luca MontebugnoliClavichord preparation and tuning: Joris PotvliegheSound editing: Tom BeghinSound mixing and mastering: Steven MaesResearch assistance: Anastasios Zafeiropoulos
Abstract:Carl Philipp Emanuel Bach’s Sonatas with Varied Reprises (published in Berlin, 1760) constituted a bold experiment. Spelling out every repeat, Bach applies to each the art of variation. Starting off as a service (“play this and you’ll sound as if you’re improvising”), the opus ends up a masterclass in variation. Tom Beghin, playing his own beloved clavichord, enacts the role of the keyboardist-composer who repeats himself, while never saying the same thing twice.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850